Clinical Efficacy of Dapagliflozin in the Treatment of Patients with Diabetic Nephropathy and Its Effect on Proteinuria Level - Jin ZJ; Wang GZ (Diabetes, Metabolic Syndrome and Obesity, 2023)
Ze-Jun Jin, Gen-Zhen Wang Department of Nephrology, Anhui Wannan Rehabilitation Hospital, Wuhu, Anhui, People’s Republic of ChinaCorrespondence: Gen-Zhen Wang, Email guanpa7947285@163.comObjective: This study aimed to analyze the clinical efficacy of dapagliflozin in the treatment of diabetic kidney disease and its impact on proteinuria levels in patients.Methods: Retrospective analysis of medical records of 176 patients with diabetic kidney disease treated at our hospital from January 2020 to January 2022. According to the different treatment methods, the patients were divided into a control group (n=88) receiving enalapril maleate treatment and an observation group (n=88) receiving dapagliflozin treatment. The clinical treatment effects, blood glucose levels, renal function indicators, inflammation factor indicators, and adverse reactions were compared between the two groups.Results: The total effective rate of treatment (97.73%) in the observation group was significantly higher than that (79.55%) in the control group (P< 0.05). After treatment, the FPG, 2hPG, and HbAlc levels in the observation group were significantly lower than those in the control group (P< 0.05). After treatment, the Scr, BUN, UmAlb, UAER, UACR, and 24-hour urine protein quantitative levels in the observation group were significantly lower than those in the control group (P< 0.05). After treatment, the hs-CRP, IL-1β, and TNF-α levels in the observation group were significantly lower than those in the control group (P< 0.05). The incidence of adverse reactions in the observation group significantly lower than the control group (P< 0.05).Conclusion: Compared with enalapril maleate alone, the combined application of dapagliflozin in the treatment of diabetic kidney disease has more significant clinical efficacy. It can further control patients’ blood sugar, reduce their body’s inflammatory response, alleviate or eliminate their proteinuria symptoms, promote the recovery of their renal function, and enhance the safety of their treatment to a certain extent, which helps to further improve the clinical treatment effect of patients.Keywords: stroke, nursing, hemiplegic limb rehabilitation training nursing, effect analysis